The Role of Christian Religious Education in Encouraging Inclusive Attitudes among Elementary School Students in Indonesia - Panggabean, Eva Saryati (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
This study aims to analyze the role of Christian Religious Education (PAK) in fostering inclusive attitudes in Indonesian elementary schools. Employing a qualitative approach, this research conducts a literature review of various national and international studies and publications. The findings suggest that PAK, when implemented in an open, dialogical, and collaborative manner, has significant potential in shaping inclusive attitudes among students from diverse backgrounds and across different religions. PAK instruction that incorporates multicultural values, tolerance, and anti-discrimination principles has proven to be an effective agent in promoting harmony within diversity and preventing exclusive attitudes. Moreover, collaborative strategies involving different school and community stakeholders are identified as essential to the successful implementation of inclusive education. The study recommends the development of a PAK model that is responsive to diversity and the strengthening of teachers’ capacity as key actors in promoting inclusive education at the elementary level in Indonesia.